Effect of Residence Time of Graphitisation on Thermal Conductivity of Molded Graphite - Pedy Artsanti; Yateman Arryanto; Kusnanto Kusnanto (Indonesian Journal of Chemistry, 2001)
The effect of residence time of graphitisation on thermal conductivity of molded graphite has been examined. The examination has been conducted by varying residence time of graphitisation of molded carbon with petroleum coke as raw material and coal tar pitch. Graphitisation has been conducted by heating molded graphite at 2500 °C in argon atmosphere with residention time of 10, 30 and 90 minutes. Graphitisation degree, density, shrinking mass and porosity of molded graphite were examined and so was its thermal conductivity. The result showed that the decrease of porosity and the increase of graphitisation degree due to the increasing of residention time of graphitisation will increase the thermal conductivity of graphite. Molded graphite graphitisized with residence time for 90 minutes residention time gave thermal conductivity of 2.134 Watt/mK and graphitization degree 0.718.